2022
DOI: 10.1111/ddi.13581
|View full text |Cite
|
Sign up to set email alerts
|

Most lichens are rare, and degree of rarity is mediated by lichen traits and biotic partners

Abstract: Aim Understanding ecological distributions of global biodiversity is stymied by incomplete knowledge of drivers of species rarity. These include trade‐offs among life‐history traits that impact dispersability, competition, reproductive output and speciation and extinction. In this study, we aim to understand potential drivers of rarity in North American lichens. Location and methods With nearly 5500 species and a third of global species richness, North America is a hotspot for lichen biodiversity. Here, we emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…The role of pyrenoids and other CCMs in driving lichen distributions in eastern North America to likely apply much more broadly around the world. Recent studies have highlighted the differences between Trentepohlean lichen distributions and other green algal lichen taxa (Manzitto-Tripp et al, 2022), and our results suggest that those same studies might find similar patterns within the chlorococcoid chlorolichens that are currently masked by the predominance of a few CCM-containing genera (e.g., Trebouxia). A recent study in the Brazilian Atlantic Forest found decreasing presence of CCMs with canopy closure (Koch et al, 2022).…”
Section: Discussionsupporting
confidence: 81%
“…The role of pyrenoids and other CCMs in driving lichen distributions in eastern North America to likely apply much more broadly around the world. Recent studies have highlighted the differences between Trentepohlean lichen distributions and other green algal lichen taxa (Manzitto-Tripp et al, 2022), and our results suggest that those same studies might find similar patterns within the chlorococcoid chlorolichens that are currently masked by the predominance of a few CCM-containing genera (e.g., Trebouxia). A recent study in the Brazilian Atlantic Forest found decreasing presence of CCMs with canopy closure (Koch et al, 2022).…”
Section: Discussionsupporting
confidence: 81%
“…This reflects the ease of collection and detection for macrolichens, the emphasis on sexual characters in taxonomic frameworks, and the perception that asexually reproducing lichens are both difficult to identify and evolutionary dead ends (Poelt 1970;Bergamini et al 2005Bergamini et al , 2007Tripp 2016;Lu ¨cking et al 2021;Lendemer and Coyle 2021). Yet, in most North American systems, macrolichens are less species rich than crustose microlichens, and taxa with dominant asexual reproductive modes represent a more substantial component of biological diversity than has previously been believed (e.g., Lendemer et al 2016a;Lendemer 2018;Tripp et al 2019Tripp et al , 2022Waters and Lendemer 2019). The intersectionality of crustose microlichens with dominant asexual reproductive modes has resulted in major knowledge gaps for a group of ecologically important and species-rich fungal mutualisms (Hodkinson and Lendemer 2012;Allen and Lendemer 2022).…”
mentioning
confidence: 99%
“…Temperate eastern North America hosts the highest diversity of lichens on the continent, including many microlichens with dominant asexual reproductive modes (Tripp et al 2022). Intensive studies during the last two decades have substantially improved understanding of the diversity and distributions of these organisms (e.g., Lendemer 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations